Resistance to Synthetic Pyrethroids in Aedes aegypti (Diptera: Culicidae) in Thailand - Sirisopa, Patcharawan; Thanispong, Kanutcharee; Chareonviriyaphap, Theeraphap; Juntarajumnong, Waraporn (Agriculture and Natural Resources, 2014)
The insecticide susceptibility level of mosquito populations is one of the major factors inﬂ uencing the success of vector control. In this study, Aedes aegypti from seven localities with a current dengue outbreak in Thailand were subjected to synthetic pyrethroid insecticide susceptibility assays. The results revealed that Ae. aegypti from all localities were strongly resistant to bifenthrin, permethrin and deltamethrin. High resistance to lambda-cyhalothrin was detected from all localities with the exception of Ae. aegypti from Bangkok and Uttaradit which demonstrated incipient resistance. However, Ae. aegypti from Bangkok, Phra Nakhon Si Ayutthaya, Sakon Nakhon and Chumphon showed incipient resistance to alpha-cypermethrin whereas Ae. aegypti collected from Uttaradit, Mukdahan and Phatthalung were susceptible. In addition, Ae. aegypti from Bangkok, Phra Nakhon Si Ayutthaya and Uttaradit demonstrated incipient resistance to cypermethrin while susceptibility of Ae. aegypti from Mukdahan, Sakon Nakhon, Phatthalung and Chumphon to cypermethrin was observed. It was concluded that ﬁ eld-collected Ae. aegypti from all localities had developed resistance to the synthetic pyrethroids, with the majority of these being to bifenthrin, permethrin and deltamethrin.